Validitas Pengembangan Mobile Learning Berbasis Moodle di Sekolah Menengah Kejuruan Pariwisata Aisyiyah Pada Mata Pelajaran Pengetahuan Bahan Makanan - Titen Darlis Santi; Anni Faridah (Universitas Pancasakti Tegal, 2021)
The use of learning media in Aisyiyah Tourism Vocational School is still dominant in using printed books and less using mobile-based learning media, so it is felt to be less effective in learning and makes students passive. So the development of Moodle-based Mobile Learning media is necessary for the learning process. The purpose of this research is the development of Moodle-based Mobile Learning in Aisyiyah Tourism Vocational School in the subject of valid Food Ingredients Knowledge. The development method is R&D for education, with the Four-D development model. Data retrieval was carried out by giving instruments to validators of media experts and material experts, data analysis using Aikens V, the research location was Aisyiyah Tourism Vocational School, West Sumatra, class X-cooking class students. The results of research on Moodle-based Mobile Learning learning media as interactive media from product validity tests based on media validation an average of 0.92 is declared